1994
DOI: 10.1111/j.1574-6976.1994.tb00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical diversity among sulfur-dependent, hyperthermophilic microorganisms

Abstract: Hyperthermophiles are a recently discovered group of microorganisms that grow at and above 90 degrees C. They currently comprise over 20 different genera, and except for two novel bacteria, all are classified as Archaea. The majority of these organisms are obligately anaerobic heterotrophs that reduce elemental sulfur (S degree) to H2S. The best studied from a biochemical perspective are the archaeon, Pyrococcus furiosus, and the bacterium, Thermotoga maritima, both of which are saccharolytic. P. furiosus is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 89 publications
1
37
0
Order By: Relevance
“…In an attempt to enhance the growth yields of P. furiosus, the addition of salts of elements such as V, Se, Cs, F, Pb, Rb and additional Ni to the mineral salts solution were unsuccessful, whereas the addition of W (10 /xM) and additional Fe (final concentration, 25 /zM) to the growth medium gave a 5-10 fold increase in cell yields (wet weight) from large scale fermenter runs. Although the effect of W on growth kinetics and final cell densities were not reported, this preliminary study clearly indicated a role for W in the metabolism of P. furiosus, and perhaps in other heterotrophic archaea ( [126], reviewed in [22,[36][37][38][129][130][131][132][133]). Moreover, it led to the purification of the first W-containing iron-sulfur protein from this organism [31 ].…”
Section: Hyperthermophilesmentioning
confidence: 94%
“…In an attempt to enhance the growth yields of P. furiosus, the addition of salts of elements such as V, Se, Cs, F, Pb, Rb and additional Ni to the mineral salts solution were unsuccessful, whereas the addition of W (10 /xM) and additional Fe (final concentration, 25 /zM) to the growth medium gave a 5-10 fold increase in cell yields (wet weight) from large scale fermenter runs. Although the effect of W on growth kinetics and final cell densities were not reported, this preliminary study clearly indicated a role for W in the metabolism of P. furiosus, and perhaps in other heterotrophic archaea ( [126], reviewed in [22,[36][37][38][129][130][131][132][133]). Moreover, it led to the purification of the first W-containing iron-sulfur protein from this organism [31 ].…”
Section: Hyperthermophilesmentioning
confidence: 94%
“…95 Many Archaea were initially described as being obligately dependent on S 0 reduction for the production of energy. 61 However, Bonch-Osmolovskaya and Stetter showed that some so-called "sulfur-dependent" Archaea grow well in co-culture with hydrogen-using thermophilic methanogens in the absence of sulfur. This is possible through interspecies hydrogen transfer, whereby growth-inhibiting hydrogen (from H + used as an electron acceptor) is removed without sulfur serving as the electron acceptor.…”
Section: Metabolic Diversity Of Thermophilic Anaerobesmentioning
confidence: 99%
“…The occurrence of the ED cycle was initially demonstrated in Xanthomonas phaseoli [73]. It is known to operate also in other proteobacteria^including Acetobacter, Agrobacterium, Azotobacter, Pseudomonas, Rhizobium, Thiobacillus [72], and other Xanthomonas species (Letisse and Lindley, personal communication)^but it has not been reported so far in other ED-utilising species, including the archaebacteria currently under investigation [74,75], or in other bacteria and fungi. Bacteria utilising the ED cycle have common metabolic characteristics, including the preferential utilisation of organic acids over carbohydrates and the ability to synthesise exopolysaccharides.…”
Section: The Ed Cyclementioning
confidence: 99%